Analysis of learning implementation according to Jean Piaget's Theory in the context of elementary school children's cognitive development. - Yanti, Yuli; Hidayah, Nurul; Nur Kalifah, Diah Rizki; El Fiah, Rifda; Mardiyah, Mardiyah; Zulaiha, Siti; Ninda Uminar, Ajeng (Universitas Islam Negeri Raden Intan Lampung, 2024)
Background: Learning at the elementary school level plays an important role in forming children's cognitive foundations. One of the prominent theories in understanding children's cognitive development is Jean Piaget's theory. This theory emphasizes that learning must be adapted to the child's stage of cognitive development to achieve optimal results.Aim: To analyze the implementation of learning according to Jean Piaget's theory in the context of cognitive development of elementary school children Method: Qualitative research method with library research type . The research objects are elementary school students, teaching and learning activities, and teaching materials. Data was collected via Google Scholar , Researchgate , Science Direct , and Semantics . Data analysis uses content analysis .Results: The cognitive abilities of elementary age children vary at each age level. Piaget in his theory that in elementary age children, children's cognitive development is divided into 2 stages, namely concrete operations which occur at the age of 7 years to 11 years, in this stage children are able to think about things that are logical, rational, scientific and objective at every thing that is real. The KBM process carried out must be contextualized in real life. The second is the formal operational stage, which occurs in children aged 11 to 12 years and over. In this stage, children begin to be able to think about things that will happen in the future and things that are imaginary or imagined. In the teaching and learning process, children can apply constructivist and inquiry learning models which in principle require high levels of reasoning and require students to actively think, think and draw meaning from empirical and abstract things.Conclusion: The application of Piaget's theory in elementary schools has a positive impact on children's cognitive development. Teachers who adapt learning methods according to students' cognitive development stages are able to help children understand the material better, improve critical thinking skills, and make the learning process more effective and enjoyable.